(3QSGdI OYhI GdCWHGAs - (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s ((3TgGH GdOjf GdbOS s)
(3ChdgG (B:s
(3QSGdI OYhI GdCWHGA Ydi ePgH UGMH cdjdI hOefI ef abQ GdMceGA hcdGe GdHdZGA hfhGOQ GdadGSaI s
(3BNQgG (B:s
(3heQGO GdfaS hebQ GdCfS ai edchJ GdSeGA MjK dGjJYPQ eWdhH hdG jabO eMHhH Efg SejY eLjH JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3CdagG GHf HWdGf ddCejQ fGUQ GdOhdI CHj fUQ CMeO Hf eQhGfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B756s
Keywords: (3GdWHs